Defining Strategic Position and Busines Model of CV Energi Selaras Alam (The Indonesian Journal of Business Administration, 2013)
Fuel –addictive industry is a growing industry in Indonesia. With potential market of 80 million vehicles in Indonesia where most modern car use a subsidized –low quality fuel, market opportunity of this industry is very big. Although this industry is very influenced by world oil price and government regulation about subsidized fuel. CV.Energy Selaras Alam is the new comer in this industry. Founded in 2011, this firm provides a low price and highly efficient octane booster product to the society. Along the decreased issue of subsidized fuel price, this firm difficult to maintain their sales growth and expand to broader market that leads to significant decrease on its profit. If this condition allowed for the next couple month, this will lead company to bankruptcy.To understanding company’s condition better, this research use methods of observation, literature survey and interview. Resource analysis and value chain analysis are used for internal analysis. PESTEL, Porter’s 5 forces, and strategic group are used for external analysis. By using interrelationship diagram, it known that the root cause of this company’s issue is the un-clarity of its strategic positioning.To formulate the solution, SWOT, IFAS, EFAS and SFAS matrix used to find CV.ESA new strategic position. Alternative strategy is generated from TOWS Matrix, result 13 strategies. Every strategy is integrated and mapped back into a new business model to create more integrated result for this company. The conclusion from this proposed strategy is the new strategy of CV ESA will be based on cost focus strategic position. This new strategy proposed to diversify product and marketing channel that focus on car and motorcycle user and also local industry that located only in West Java. Action Plan is derived from business model formulation, and prepared for 3 year implementation Plan. The implementation plan of those strategies is suggested to adjust the number of marketing and sales armada. This armada will be focused on creating new alliances and partnership that will be a success foundation of strategy proposed. Strategic Implementation will be implemented in the next 3 years and will start in 2013. Hopefully, this Research result would contribute a better understanding related with the importance of Strategic position and business Model in Startup Company Key Words: Startup Company, strategic positioning, business model, Fuel addictive, Octane Booster.